دور القاضي الجزائري في مجال التحكيم الدولي - تخنوني, أسماء (University of Eloued جامعة الوادي, 2018)
إن نظام "التحكيم" في العالم كبديل لحل النزاعات يرتبط أساسا بتطور الاجتهاد القضائي "القضاء الفرنسي أنموذجا"، سواء من خلال تصور حدود مجال إعمال قواعده ، أو عبر قبول نفاذ أحكامها ، وإلزام الأطراف الذين ارتضوا وسيلة التحكيم لحل منازعاتهم على تنفيذ مقرراته ، والكل لا يمكن أن يتحقق إلا من خلال رقابة قضائية متزنة وحكيمة ، تدرك أهمية نظام "التحكيم "كخيار لفض المنازعات ، وكمؤشر على التنمية الاجتماعية ، الثقافية ، الاقتصادية، السياسية، والأمنية وطنيا ودوليا، كما يعتبر اتفاق التحكيم الحجر الأساس أو مركز الثقل في بناء التحكيم كنظام لحل نزاعات التجارة الدولية . Abstract The "arbitration" in the world system as an alternative to resolve disputes is mainly related to the development of jurisprudence, "the French judiciary as a model", Either by concealing the limits of the scope of its rules، or by accepting the entry into force of its provisions, and to oblige parties who have accepted and to oblige parties who have accepted the means of arbitration to resolve their disputes to implement its decisions. This can be achieved only through judicial control, which recognizes the importance of the "arbitration" system as an option for resolving disputes. The arbitration agreement is considered to be the foundation stone or center of gravity in the establishment of arbitration as a system for resolving international trade disputes.
The role of the Algerian judge in the field of international arbitration
مجلة البحوث والدراسات المجلد 15 العدد01 جامعة الوادي
Keywords: اتفاق التحكيم ؛ شرط التحكيم ؛ مشارطة التحكيم; Arbitration agreement - arbitration clause.